Endometrial Stromal Sarcoma - A Rare Gynecological Malignancy - Maria Ishfaq; Saima Rafique; Saima Javeed; Tahira Yasmeen (Journal of University College of Medicine and Dentistry, 2022)
Endometrial stromal sarcoma is rare gynecological malignancy. A proper preoperative diagnosis is difficult and most of cases diagnosed on histopathology. This is case of endometrial stromal sarcoma infiltrating to both ovaries that is stage II A.A 44year old female presented with complaint of irregular heavy vaginal bleeding and history of loss of weight, appetite and altered bowel habits. Clinical diagnosis of Leiomyosarcoma was in mind but on histopathology endometrial stromal sarcoma infiltrating to both ovaries confirmed.